The pertussis paradox: why are cases increasing despite vaccination efforts? - Błaszczyszyn, Katarzyna; Bolek, Monika; Muc, Katarzyna; Hopej, Natalia; Dobrzeniecki, Krzysztof; Turek, Kacper (Quality in Sport, 2024)
Introduction Pertussis, a highly transmissible respiratory infection mainly caused by Bordetella pertussis, remains one of the most widespread public health concerns despite the establishment of global vaccination initiatives. The disease manifests as paroxysmal coughing followed by a characteristic high-pitched “whooping” sound, and post-tussive vomiting. Severe complications can include pneumonia, encephalopathy, and even mortality, particularly in infants. Aim of the study This study aims to provide a comprehensive analysis of pertussis, encompassing its clinical presentation, complications, diagnostic methods, epidemiological aspects, and vaccination strategies, with a special focus on the development and potential impact of a novel nasal pertussis vaccine. Brief description of the state of knowledge Diagnosis of pertussis often relies on recognizing typical symptoms supported by laboratory confirmation through culture methods, polymerase chain reaction testing, or enzyme–linked immunosorbent assays. This disease leads to considerable morbidity and mortality worldwide, accompanied by profound medical, social and economic challenges. Summary To address the limitations of existing vaccines, a novel nasal pertussis vaccine has been proposed. This vaccine aims to elicit robust mucosal immune responses, thereby providing enhanced protection against infection and preventing the asymptomatic transmission of Bordetella pertussis. The study offers a detailed examination of pertussis and comprehensive statistics to support the analysis, providing valuable insights into the epidemiology, highlighting the need for improved vaccination strategies to mitigate the disease’s impact.